A Region of Regimes : Prosperity and Plunder in the Asia-Pacific - Pempel, T. J., 1942- (Book collections on Project MUSE., 2021)
"Decades of rapid economic growth in East Asia mask diverse national paths. Analyzing ten countries over forty years, the book identifies three major regime types and their discrete economic paradigms, some vastly successful, others mired in failure. In closing, the book shows how shifting combinations of regimes shaped changes in the regional order"--